Protective effects of cordycepin pretreatment against liver ischemia/reperfusion injury in mice. Issue 3 (14th March 2023) - Liu, Yunxia; Sheng, Mingwei; Jia, Lili; Zhu, Min; Yu, Wenli
Abstract: Introduction: Cordycepin has been reported to exhibit hepatic protective and anti‐inflammatory properties. Here, we investigated the role of cordycepin in ischemia/reperfusion (IR)‐induced liver injury in a mouse model. Methods: Mice were pretreated with cordycepin by gavage for 3 weeks, followed by the establishment of the IR modeling. Liver injury, Suzuki's histological grading, hepatic apoptosis, and inflammatory responses were evaluated by biochemical and pathological analysis. Results: It was found that Cordycepin pretreatment at 50 mg/kg for 3 weeks attenuated IR‐induced liver injury, as reflected by the significant decrease of the levels of aspartate aminotransferase, alanine transaminase, lactate dehydrogenase, and low‐density lipoprotein. Cordycepin pretreatment also reduced histopathological changes, attenuated hepatocyte apoptosis, inflammatory responses in the livers of IR mice. Mechanically, toll‐like receptor 4/nuclear factor kappa‐B signaling in liver tissues was inhibited by Cordycepin pretreatment. Conclusions: In conclusion, Cordycepin pretreatment protects IR‐induced liver injury, which demonstrates its potential for the treatment of IR in the liver. Abstract : Cordycepin pretreatment reduced apoptosis and inflammation markedly in ischemia/reperfusion (IR) liver. Cordycepin protects and improves liver functions in IR mouse model.